Impact of NPM1 mutation subtypes on treatment outcome in AML: The Lyon-University Hospital experience. (January 2019) - Heiblig, Maël; Sujobert, Pierre; Hayette, Sandrine; Balsat, Marie; Elhamri, Mohamed; Salles, Gilles; Thomas, Xavier
Highlights: Type A NPM1 mutation is found in 73% of cases and non-type A mutations in 27%. Achievement of MRD-negativity after intensive chemotherapy is of favorable prognostic value in terms of survival. MRD-negativity is obtained significantly earlier in patients with type A mutation. A better median survival is observed in patients with non-type A NPM1 mutations.